E-learning: past, present and future / Saliyah Kahar - Kahar, Saliyah (2004)
Throughout history technological advances have had a dramatic impact on society. New technology has also had an impact on education in the past. But what will the new technologies invented today and tomorrow do for learning in the future? Of course, we can only predict what will happen, but in this paper I will present a few current elearning trends and try to look into the future to see how online education and e-learning could change in the years to come. I will mostly look at new and future technologies for learning - "old" technologies like the web is not mentioned much even though it will probably have a significant role in the future too. In this paper I also try to give a lot of examples, either from my own experiences or my visions about the future.